2016
DOI: 10.1002/stem.2337
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Role of Adipose-Derived Stem Cells in Staphylococcus aureus-Induced Lung Injury is Mediated by RegIIIγ Secretion

Abstract: Effective and specific therapeutic approaches are still needed for treating acute lung injury caused by severe pneumonia. Adipose-derived stem cells (ADSCs) are well-characterized adult stem cells that have antibacterial and anti-inflammatory effects. In this study, we evaluated the therapeutic effect of ADSCs on Staphylococcus aureus-induced acute lung injury in mice. Our results showed that intratracheal injection of ADSCs could attenuate the severity of lung inflammation, and reduce the bacterial load as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Eight‐week‐old C57BL/6 and Kit W‐sh/W‐sh mice were used to establish an S. aureus pneumonia model . In brief, 40 μL of S. aureus (5 × 10 7 CFUs) was inoculated intratracheally into anesthetized mice.…”
Section: Methodsmentioning
confidence: 99%
“…Eight‐week‐old C57BL/6 and Kit W‐sh/W‐sh mice were used to establish an S. aureus pneumonia model . In brief, 40 μL of S. aureus (5 × 10 7 CFUs) was inoculated intratracheally into anesthetized mice.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Qian et al [30] revealed that MSCs with anti-bacterial and anti-inflammatory effects could treat Staphylococcus aureus-infected mice. [30] Alcayaga-Miranda et al [3] used a combination of antibiotherapy and MSCs in an in vivo mouse model. The two treatments were strongly synergistic in terms of increasing the survival rate.…”
Section: Immunohistochemically Wounds Treated Withmentioning
confidence: 97%
“…Severe bacterial infections represent a leading cause of acute lung injury (ALI) and recent research efforts have suggested that adipose‐derived MSCs may represent a potentially exciting treatment option that takes advantage of the secretion of paracrine‐acting factors . As described in their recent STEM CELLS article, researchers from the laboratory of Feng Xu (Zhejiang University, Hangzhou, China) evaluated the therapeutic effect of MSCs on S. aureus ‐induced ALI in mice, finding that intratracheal injections of cells attenuated the severity of lung inflammation, reduced bacterial load, and improved the survival of infected mice . Mechanistically, Qian et al established that the activation of the Toll‐like receptor 2 (TLR2), myeloid differentiation primary response 88 (MyD88), and Janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) intracellular signaling cascades prompted the secretion of the regenerating islet‐derived IIIγ (RegIIIγ) from MSCs, which mediated the direct antimicrobial effects.…”
Section: Related Articlesmentioning
confidence: 99%
“…In our first Featured Article from STEM CELLS Translational Medicine , Chow et al explore the mechanisms by which MSCs augment the antimicrobial activity of various classes of conventional antibiotics, including the generation of enhanced activity against drug‐resistant strains of Staphylococcus aureus ( S. aureus ) . In a Related Article published in STEM CELLS , Qian et al demonstrated that adipose‐derived MSCs can attenuate S. aureus ‐induced lung injury and improve survival of infected mice by reducing the bacterial load and alleviating inflammatory responses through paracrine‐acting secreted factors …”
mentioning
confidence: 99%